PENGEMBANGAN MODUL PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DENGAN PENDEKATAN PROJECT BASED LEARNING BAGI SISWA SDN 22 BARINGIN KECAMATAN LIMA KAUM - Andri, Andri; Hendriani, Suswati; Fadriati, Fadriati (El -Hekam, 2019)
This research grew from inadequate learning sources availability and unmotivated learning sources for the students so that they get difficulties in understanding the material of Islamic Religious subject and Character. This problem will certainly affect the achievement of the learning process. This research aims to develop a valid learning module based project at Islamic Religious Subject and Character on the material ketika bumi berhenti berputar conducted at six grade students of SDN 22 Baringin. The method used in this research was Research and Development. This study also aims to describe about learning process on Islamic Religious Subject and Character. For collecting the data, the researcher used a Descriptive Analysis approach. Thus, it will give a product on the form of learning module based project in Elementary School. The development used in this research was 4-D model consisted of definition, design, development and dissemination. This research was carried out of its validity. This research produced a learning module based project on Islamic Religious Subject and Character at six grades students of SDN 22 Baringin. The Module validation results have been evaluated by 3 validators whose percentage is 87,78% in average and categorized as highly valid. Material development got 81,90% and was highly valid category, it was 81.48% for the presentation and was highly valid, language aspect got 86,88% and was highly valid, graphic got 100% and highly valid category and it was 88,88% for pictures and was highly valid category.